SUATU KAJIAN PLURALISME HUKUM (Upaya Mengatasi Keberagaman Hukum di Era Globalisasi) - Puspita, Lona (Fakultas Hukum Universitas Tamansiswa Padang, 2022)
Globalization brings new values into people's lives and has an impact on legal developments in various countries resulting in legal diversity (legal pluralism). The problem in this article is how to deal with legal diversity in the era of globalization? The results of the legal study can be concluded that legal pluralism does not immediately solve problems that arise in society. However, legal pluralism exists to provide a new understanding that apart from state law there are other existing legal systems in society that interact with each other and even compete with one another.